Pengendalian dan penjaminan mutu kualitas air pada wilayah Sungai Bondoyudo Baru di Lumajang dengan menggunakan metode six sigma dan PDCA - Zafira, Ayesha Tita; Iriani, Iriani (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Rivers are very important objects for several communities in the Lumajang area, because some of their activities are very dependent on rivers, resulting in environmental damage, thus affecting the quality of river water. Some residents carry out activities such as washing clothes, defecating and bathing in water sources that flow towards the river. This resulted in several rivers in Lumajang not meeting class III quality standards. In the New Bondoyudo river area in Lumajang, it is known that several parameters do not meet class III water quality standards, namely COD, DO, Total Coliform and Fecal Coliform. The aim of this research is to analyze water quality control in the New Bondoyudo river area in Lumajang to identify sigma levels that do not comply with specifications and propose improvements to reduce pollution. This data analysis uses the Six Sigma method with DMAIC stages (Define, Measure, Analyze, Improve, Control).  The results of this research obtained a sigma level value of 3.295. The main causal factors include domestic activities, industrial activities, lack of river revitalization.  In the improve stage, the PDCA (Plan, Do, Check, Act) method is used to make improvements to the water quality of the Bondyudo Baru river area in Lumajang.